Inelastic Analysis of Brick Masonry: MesolMacro-scale Approach - Shieh-Beygi, Babak (My University, 2007)
This thesis is focused on modeling of progressive failure in brick masonry structures. Two distinct strategies are examined, namely meso-modeling and macromodeling approach.
In the first part, an advanced constitutive model capable of addressing both pre and post-localization behavior is developed and implemented in a commercial finite element package. A mesoscopic modeling approach is then adopted, in which the structural behavior is examined at the level of constituents, i.e. brick and mortar. The performance of the model is verified by simulating a series of experimental tests reported in the literature. Those include the tests conducted by van der Pluijm (1993), Atkinson et al. (1989), and Page (1983).
Later, an alternative approach is developed, based on theory of homogenization, in which a lower bound assessment is employed to predict the directional strength characteristics of the brick masonry. The performance of the model is verified using numerical homogenization which involves a finite element analysis of a periodic unit cell. For both these approaches, the failure envelopes for brick masonry at different orientations of the bed joints are obtained.
Finally, a methodology is proposed for a systematic identification of material parameters of a macroscopic failure criterion describing the anisotropic strength characteristics of the brick masonry. This criterion is formulated in the framework of Critical Plane Approach (CPA) and its performance is verified against the experimental data of Page (1981 and 1983).
Keywords: Inelastic Analysis of Brick Masonary; Engineering; Engineering